AN ANALYSIS OF STUDENTS’ ABILITY IN WRITING NARRATIVE TEXT - Putri, Fatimah; Rosdiana, Rosdiana; Qarimah, Hajjatul (Jurnal Ilmiah Mahasiswa Pendidikan, 2022)
The research aims to analyze students’ ability in writing the narrative text by following the generic structure. According to the previous studies conducted by some experts, some of the students did not write the narrative text based on the generic structure. Therefore, in this research, the researcher analyzed whether students in X MIPA I at MAN 2 Aceh Besar wrote the narrative text depending on the generic structure or not. In addition, the number of students from X MIPA I was 18 students. Further, in this study, all of them participated in writing the narrative text. Additionally, the design of this study was a descriptive qualitative research design. Moreover, in collecting the data, the researcher used document analysis that would be used to get some information about students’ narrative text. In addition, the research finding showed that from 18 participants only 8 students wrote the narrative following the generic structure Furthermore, 10 of them did not write the narrative text based on the generic structure.